2003
DOI: 10.1002/cnm.628
|View full text |Cite
|
Sign up to set email alerts
|

On a finite element formulation for incompressible Newtonian fluid flows on moving domains in the presence of surface tension

Abstract: SUMMARYThis work is concerned with the numerical modelling of incompressible Newtonian uid ows on moving domains in the presence of surface tension. The solution procedure presented is based on the stabilized equal order mixed velocity-pressure ÿnite element formulation of the incompressible Navier-Stokes equations, which is adapted to a moving domain by means of an arbitrary Lagrangian-Eulerian (ALE) technique. The accurate and very robust integration in time is achieved by employing the generalizedmethod. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…The variational form (20) consists of the standard Galerkin terms summarised in G Gal , to which a stabilisation term G stab of the momentum equation has been added. In order to simplify the notation in the remainder of this section, which is dedicated to the detailed presentation of G Gal and G stab , the coupling of (20) with the deformation of the solid structure is not explicitly included.…”
Section: Finite Element Formulation For the Fluid Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The variational form (20) consists of the standard Galerkin terms summarised in G Gal , to which a stabilisation term G stab of the momentum equation has been added. In order to simplify the notation in the remainder of this section, which is dedicated to the detailed presentation of G Gal and G stab , the coupling of (20) with the deformation of the solid structure is not explicitly included.…”
Section: Finite Element Formulation For the Fluid Flowmentioning
confidence: 99%
“…Such techniques have become standard in Eulerian finite element formulations and have been applied to various problems arising in fluid mechanics (see e.g. [4][5][6][7][16][17][18][19][20][21]). A review of a variety of stabilisation techniques may be found in [22].…”
Section: Discretisation Of the Fluid Flowmentioning
confidence: 99%
“…This finding significantly simplified the problem at hand. The Lagrangian finite element simulations incorporating surface tracking technique with boundary fitted meshes are described in [9,24] for 2-D applications while in [25][26][27] the authors focus on axisymmetric problems. In recent years several authors have also described simulations of free surface flows problem with surface tension in three dimensions [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…This technique tracks a series of surface markers placed along the interface, which are advected to their new position at each time step based on the previous time step's computed interfacial velocity. Arbitrary Lagrangian-Eulerian (ALE) methods are also commonly used when surface tension effects are important (see Donea et al (2004) for an overview and Dettmer et al (2003) for an example). As the name implies, ALE methods exploit the advantages of both Lagrangian and Eulerian frames of reference to simplify the computation and maintain a high mesh quality (versus a purely Lagrangian approach) as the interface moves.…”
Section: Free Surface Capillary and Immiscible Liquid Flowsmentioning
confidence: 99%